Desenvolvimento de multicamadas metálicas do tipo Pt/Ir/Pt eletrodepositadas em titânio para eletrocatálise - Zulke, Alana Aragon (2012)
Regarding to the search for new energy sources, of renewable character, fuel cells fall into one of the most studied proposals on Electrochemistry. More specifically, the direct fuel cells (DAFCs) using short-chain alcohols as fuel, have attracted the attention of researchers over the past two decades. Problems related to the energy efficiency of Pt-based catalysts for use in fuel cells, drive several studies in the literature concerning to the modification of these catalytic systems. Thus, have been proposed in the literature, other materials than pure Pt, such as alloys in binary and ternary composition, and more recently, metallic multilayered structures(MM), the latter being the study object of this work. Platinized titanium electrodes were prepared by potentiostatic electrodeposition technique (0.05 V vs RHE), and times of 1000 sec were necessary to obtain an identical polycrystalline platinum voltammetric profile, with guaranteed reproducibility. On these substrates, Ir/Pt bilayered systems were electrodeposited controlling films thickness through the deposition charge. Calculations revealed mass loading of platinum between13.4 and 26.3 μg and maximum film thickness of 43.2 nm. AFM images confirmed the homogeneity of the coatings as well as the total covering of the substrate. A screening of variables with the aid of a 22 factorial design with central point showed better intrinsic catalytic activity (current density normalized by the electroactive area) for the Ti/Pt25mC/Ir6mC/Pt system, which answers were around 270% higher than those obtained for Ti/Pt systems. In addition to the methanol oxidation voltammetry, chronoamperometric tests of methanol oxidation and CO stripping voltammetry suggest the MM-like systems are less susceptible to the catalyst poisoning phenomenon compared to the Ti/Pt systems. Assuming that there are no area effects due the current normalization through the electroactive area, nor the possibility of a bifunctional mechanism occurring,considering that are just Pt catalytic centers exposed, an explanation for the purposes of promoting catalytic activity may be based on electronic effects due to the possible compressive stress generated by the bilayer Ir/Pt causing an energy enlargement of the d band, lowering the adsorbates energy of adsorption. EIS data indicated a lower resistance to charge transfer in the reactions performed on MM systems, which strengthens the argument regarding the positive electronic effects associated with MM-like structures.